2020
DOI: 10.11648/j.ijber.20200904.12
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tax Collection and Incentives on Economic Growth: Evidence from Nigeria

Abstract: The debate on the effectiveness of taxation as an instrument for promoting economic growth remains inconclusive, as several studies have indicated mixed effect of taxation on economic growth. Against this background this study investigated the impact of tax collection and incentives on economic growth in Nigeria. Yearly data for the period 2010-2018 was collected from the Central Bank of Nigeria and Federal Inland Revenue Service. A multiple regression model was used, tax revenue was proxied by actual total ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This study focuses on the potential of local taxes, specifically MVT, and considers the growth in the number of vehicles in the region as an important factor. Previous studies (Adegbie et al, 2022;Akanbi, 2021;Alfirman, 2003;Alsarmi & Ahemed, 2022;Aydin, 2018) have concluded that taxes play a vital role in enhancing the revenue of a region or country, thereby supporting development. This study fills a gap in the literature with a detailed analysis of the potential of MVT in Jambi Province.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on the potential of local taxes, specifically MVT, and considers the growth in the number of vehicles in the region as an important factor. Previous studies (Adegbie et al, 2022;Akanbi, 2021;Alfirman, 2003;Alsarmi & Ahemed, 2022;Aydin, 2018) have concluded that taxes play a vital role in enhancing the revenue of a region or country, thereby supporting development. This study fills a gap in the literature with a detailed analysis of the potential of MVT in Jambi Province.…”
Section: Introductionmentioning
confidence: 99%
“…Akanbi, (2020) argued that income tax revenues used to develop and maintain infrastructure, such as roads, bridges, airports, and communication networks. This infrastructure is crucial for attracting businesses, facilitating trade, and improving productivity all of which contribute to economic growth Brondolo, (2009).…”
mentioning
confidence: 99%